2019
DOI: 10.1002/ece3.5678
|View full text |Cite
|
Sign up to set email alerts
|

Ocean warming and acidification alter the behavioral response to flow of the sea urchin Paracentrotus lividus

Abstract: Ocean warming (OW) and acidification (OA) are intensively investigated as they pose major threats to marine organism. However, little effort is dedicated to another collateral climate change stressor, the increased frequency, and intensity of storm events, here referred to as intensified hydrodynamics. A 2‐month experiment was performed to identify how OW and OA (temperature: 21°C; pHT: 7.7, 7.4; control: 17°C‐pHT7.9) affect the resistance to hydrodynamics in the sea urchin Paracentrotus lividus using an integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 111 publications
(180 reference statements)
1
10
0
Order By: Relevance
“…Although in our study pH significantly influenced respiration rate after 21 days, no significant effects of pH were observed after 40 days of exposure. This suggested that both male and female P. lividus have the potential to acclimate at low pH conditions after prolonged exposure, as already observed for the same species, both in a laboratory 2-months exposure (Cohen-Rengifo et al 2019) and in specimens from CO 2 vents at Ischia Island (Migliaccio et al 2019). Similarly, in other species, namely E. mathaei, Strongylocentrotus fragilis, Strongylocentrotus droebachiensis, and Echinometra sp.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…Although in our study pH significantly influenced respiration rate after 21 days, no significant effects of pH were observed after 40 days of exposure. This suggested that both male and female P. lividus have the potential to acclimate at low pH conditions after prolonged exposure, as already observed for the same species, both in a laboratory 2-months exposure (Cohen-Rengifo et al 2019) and in specimens from CO 2 vents at Ischia Island (Migliaccio et al 2019). Similarly, in other species, namely E. mathaei, Strongylocentrotus fragilis, Strongylocentrotus droebachiensis, and Echinometra sp.…”
Section: Discussionsupporting
confidence: 69%
“…Only extremely low pH (6.6) negatively affected righting time in S. fragilis (Taylor et al 2014 ). Other behavioural aspects in P.lividus were recently investigated by Cohen-Rengifo et al ( 2019 ). They showed that podia adhesion strength was not influenced by reduced pH and highlighted positive synergistic effects of ocean acidification and ocean warming on sea urchin moving velocity at 7.7 pH, but not at 7.4 pH.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, larvae of the sea urchin Arbacia lixula grown at low pH exhibited reduced arm length (Foo et al, 2020). Although it was demonstrated that under near-and far-future ocean warming and acidification scenarios individuals of Paracentrotus lividus fully balanced their acid-base status, their skeletal growth was halved after 60 days (Rengifo et al, 2019). Thus, it is evident that the study of the effects of multi-stressor scenarios is crucial to have a realistic scheme of the impact that human activities are causing to aquatic life.…”
Section: Introductionmentioning
confidence: 99%